KUALITAS SEMEN SEGAR KAMBING KACANG DENGAN LAMA SIMPAN YANG BERBEDA PADA SUHU RUANG MENGGUNAKAN PENGENCER TRIS AMINOMETHAN KUNING TELUR - Kris, Utomo (Jurnal Sains Peternakan, 2014)
This aim of research intent to know fres sperm quality Kacang goat on storage different storage time on room temperature using yolk tris aminomethan extender. This research is done at the laboratory of Animal Husbandary faculty at the Kanjuruhan University on the 2th until 30th August 2012. Observational method that is utilized is experimental method by use of Fledged Random Design (RAL). Each treatment was repeted 5 times. Base on the result of research showed that spermatozoaâs quality Kacang goat on room temperature with different storage time using yolk tris aminomethan extender (P<0,01). This research has high motilitass and viabilitas spermatozoaâs Kacang goat onÂ  fresh sperm quality with different storage time on room temperature using yolk tris aminomethan extender (P<0,01). But on spermatozoas abnormality Kacang goat on room temperature using yolk tris aminomethan extender (P<0,01).Â Key word : Kacang goat, Sperm quality, Room temperature, fresh sperm, yolk tris aminomethan